PERAN DATA STORE DALAM MEMPRESENTASIKAN HUBUNGAN DATA FLOW DIAGRAM SSADM DENGAN ENTITY RELATIONSHIP DIAGRAM - Rizki Ridwan; Nunu Kustian; Erlin Windia Ambarsari (Lembaga Pengembangan Kinerja Dosen, 2022)
The information system development step often used is the System Development Life Cycle (SDLC). One of the SDLC stages is system design. It uses the Data Flow Diagram version of the Structured System Analysis and Design Methodology (SSADM) because it is a traditional model closely related to the waterfall model. This study aims to prove the role of the data store in the DFD and become an entity in the Entity-Relationship Diagram (ERD) to see the relationship between each entity. Benefit the associative method tests the connection of the data store on the DFD, which is realized to the ERD. The results obtained are the role of the data store in the DFD to become an entity on the ERD with a proven query table to facilitate data retrieval. Keywords: Entity Relationship Diagram, Data Flow Diagram, SDLC, SSADM